The influence of deposition parameters and crystallinity of copper substrate on the formation of APCVD derived graphene - Mohamad Shukri bin Sirat (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Since its debut in 2004, graphene has created a 'gold rush' in the researches world due to its superlative characteristics that could benefit a lot in many application such as electronics and aerospace. In order to utilize its characteristics into commercial applications, a large scale production of graphene with high quality is necessary. Chemical vapor deposition (CVD) has been reported to be one of the suitable methods to produce graphene in a large scale through decomposition of methane gas, CH4 at high temperature with the presence of transition metals such as Cu as the catalyst. Typically, the graphene produced is polycrystalline which consists of many small graphene domains that could deteriorate its performance. It is believed that the polycrystallinity of the graphene was produced due to the usage of polycrystalline substrates that might influence the growth of the graphene during CVD. Hence, this study intends to investigate the effects of Cu substrate crystallinity towards formation of graphene in CVD. The graphene was deposited in a closed reactor at 1000 ˚C with the presence of argon (Ar), hydrogen (H2) and methane (CH4) gases of 0.6:0.2:0.2 gas ratios for 30 minutes. The Cu substrates were varied into polycrystalline and single crystal Cu of (100),(110) and (111) orientations. The as-grown graphene was then analyzed using Raman spectroscopy and the optical microscope (OM). The Raman spectra show the existence of graphene peak for all the Cu substrates. The calculation of ID/IG ratio revealed that the polycrystalline Cu possessed the lowest amount of defects followed by Cu(100), Cu(110) and Cu(111). Besides that, I2D/IG ratio fluctuated between 0.22 to 0.34 suggested that the surface orientation is not a major factor that could control the graphene layer thickness at these reaction conditions. It is understood that at high CH4 concentration, lattice mismatch plays an important role in controlling the growth of the graphene. Large lattice mismatch of Cu(111) causes a highly defective graphene to be produced. These findings thus would give a new insight in the understanding of the graphene growth at high CH4 concentration in CVD.